Sustainable development and higher education institutions: A challenge to fulfill - Fleig, Raquel; do Nascimento, Iramar Baptistella; Michaliszyn, Mario Sergio (Education Policy Analysis Archives, 2021)
Public educational policies, together with the university, expand subsidies to civilizational progress and national development. Around the world, universities began to participate in actions aimed at meeting the goals of Sustainable Development driven by initiatives supported by the United Nations. This article aims to identify, through scientific bibliography, the implementation of the theme: sustainable development in higher education institutions in several countries. This is an integrative review, carried out on the databases: Web of Science and Scopus. The descriptors and strategies used to search the databases were: sustainability AND universities AND sustainable development AND higher education; the terms translated into English and the Boolean 'OR' were used for all descriptors. After evaluating the selection criteria, a total of 34 articles were selected for the study. The results have shown that the practice of including the theme develops slowly and progressively in higher education institutions. It is concluded that sustainable development is a theme that requires multidisciplinarity, transdisciplinarity, and interdisciplinarity since it adds the need for knowledge and attitudes that enhance work between managers and teachers in the academic scenario. The partnership between universities, government, and companies can be an essential factor in the integration of sustainable development in higher education institutions, mainly in developing countries, and that many studies and advances are necessary for sustainable development to be carried out within a dynamic conception in universities. <!--[if !supportLineBreakNewLine]--> <!--[endif]-->